Transporte urbano de baixo carbono na cidade de S??o Paulo: an??lise das pol??ticas p??blicas locais - Maglio, Leonardo Machado (2019)
Especially in big cities, where vehicles which run on f??ssil fuels are largely used, transportation accounts for 23% of the global emission of greenhouse gases ??? GEE. So, we can say that transportation in the city of S??o Paulo is closely related to the emission of GEE as well. In the last ten years, however, major efforts have been made by the government to develop important political instruments to face this kind of problem. Consonant with such efforts, the study here under consideration, aims to focus on analyzing public policies which have the decrease of the emission of greenhouse gases (GEE), as regards urban transportation, as their goal; it also aims at presenting measures to be implemented by the city to decarbonizing urban transport. This exploratory research is based on a research conducted on documents about related legislation, plans and programs developed by the City Hall of S??o Paulo. The ???Gesellschaft F??r Zusammenarbeit??? ??? GIZ ??? was used as a guideline to support this kind of approach. GIZ proposes the use of the A-S-I Framework when planning public policies which focus on the use of low carbon urban public transportation; it uses five different types of political instruments to promote the reduction of such kind of emission: Planning, Regulatory, Economic, Information and Technological. The outcomes of the present research show that the planning of the use of the soil is the most advanced measure for decarbonisation of the urban transport sector in the city. To reach this goal, the government should also prioritize the implementation of, as well as the improvement of the existing urban railway network, the revision of people???s expenditure on public transportation and how it affects them, the legalization of ???micromobility???, and the definition of ??reas of low level of carbon emission.